Conflict In James Marsh’s Movie: Theory Of Everything Movie Script - Gorang, Engelbert Aldo Saputra; Moelier, Dahlia D.; Rijal, Tabhan Syamsu (Fakultas Sastra, Universitas Bosowa, 2024)
The research aims are to identify the types of conflict and factors that exists in the Anthony McCarten’s movie script “Theory of Everything”. The writer used the conflict theory of Ursula Lehr to find out the conflicts and factors that exists in the movie script. The primary data is from the movie script written by Anthony McCarten which directed by James Marsh. The writer used the descriptive qualitative method in presenting this research. The results of the research, the writer found there were 6 types of conflict found in The Theory of Everything, they were conflicts in religions, personal conflict, conflict with other people, conflict with husband/wife, conflict with relatives and conflict with parents. The factors of conflicts are personal needs and goals, beliefs and values, disability and physical health, family dynamics, communication, emotional factors. In the end, the movie honors how resilient the human spirit can be when faced with hardship. It shows how people like Stephen Hawking overcome great obstacles with bravery, tenacity, and unwavering devotion to their own convictions and goals. Through this research, the writer wishes that the readers can understand the application of the Conflict theory by Ursula Lehr in finding the conflict.